2009
DOI: 10.1074/jbc.m808360200
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock Components CRY1 and CRY2 Are Necessary to Sustain Sex Dimorphism in Mouse Liver Metabolism

Abstract: In mammals, males and females exhibit anatomical, hormonal, and metabolic differences. A major example of such sex dimorphism in mouse involves hepatic drug metabolism, which is also a noticeable target of circadian timekeeping. However, whether the circadian clock itself contributes to sex-biased metabolism has remained unknown, although several daily output parameters differ between sexes in a number of species, including humans. Here we show that dimorphic liver metabolism is altered when the circadian regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 53 publications
5
71
0
1
Order By: Relevance
“…Food timing is known to have profound influences on obesity and metabolic dysfunction (3,22). However, although Cry1/2 Ϫ/Ϫ mice display arrhythmic feeding when fed standard chow, they remain lighter than controls and only develop obesity under HFD challenge (7). This highlights the importance of diet under conditions of circadian disruption, such as that seen with shift-working individuals.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Food timing is known to have profound influences on obesity and metabolic dysfunction (3,22). However, although Cry1/2 Ϫ/Ϫ mice display arrhythmic feeding when fed standard chow, they remain lighter than controls and only develop obesity under HFD challenge (7). This highlights the importance of diet under conditions of circadian disruption, such as that seen with shift-working individuals.…”
Section: Discussionmentioning
confidence: 88%
“…Brd mice (7,10). To close this gap, the current study characterizes the response of Cry1/2 Ϫ/Ϫ mice to diet-induced obesity, providing mechanistic insight into the physiological anomalies seen under these conditions.…”
mentioning
confidence: 99%
“…GCL is composed of a catalytic (GCLC) expressions of Gclc and Gclm were circadian-regulated in both sexes. In mice, the circadian clock components, Cry1 and Cry2, are suggested as a prerequisite for sustaining sex dimorphism in the liver metabolism (Bur et al, 2009). In human beings, sex dependency of circadian pharmacology has been observed in a Phase III clinical trial for chronomodulated therapy of metastatic colorectal cancer (Giacchetti et al, sexual dimorphism and the circadian timing system are generally interconnected in both humans and rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have previously reported that the circadian rhythms of hepatic P450 activities in rats are obvious in males but not in females (Furukawa et al, 1999c). In mice, the circadian clock components, Cryptochrome 1 and 2 (Cry1 and Cry2), are suggested as a prerequisite for sustaining sex dimorphism in the liver metabolism (Bur et al, 2009). Furthermore, sex dependency of circadian pharmacology has been observed in a Phase III clinical trial for chronomodulated therapy of metastatic colorectal cancer (Giacchetti et al, 2006).…”
mentioning
confidence: 99%
“…Cry1/Cry2 double KO mice (53) in the C57BL/6J genetic background are described in ref. 54. Unless noted otherwise, mice were maintained under standard animal housing conditions with free access to food and water and in 12-h LD cycles.…”
Section: Methodsmentioning
confidence: 99%